Gondra's Exploration of Tube Volume - Juraganda S, Chandra Saptanto; Tambunan, Hardi; Simanjuntak, Ruth M (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to explore students' understanding of the concept of cylinder volume through a contextual approach based on the fictional character